Temperature measurement system for building material and built space thermal evaluation / Zainazlan Md Zain ... [et al.] - Md Zain, Zainazlan; Taib, Mohd Nasir; M. S. Baki, Shahrizam; Ahmed, Azni Zain (Institute of Research, Development and Commercialisation (IRDC), 2006)
This paper examines the temperature profile of a building material and also a built space. The study directly examines the influence of solar radiation on building material and the heat it generated and diffuses into the built space. Two experiments are presented. The first look at a simple technique for evaluating heat performance of a building material, and the second evaluates the performance of a cross-ventilated built space with respect to solar radiation.